2017
DOI: 10.1136/bcr-2016-217211
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin therapy effective in a patient with depletion syndrome from secretory villous adenoma

Abstract: This paper details the case of a 26-year-old woman with depletion syndrome and the effectiveness of her treatment with indomethacin. Villous adenomas are benign neoplasms with a high incidence of becoming malignant. A small percentage of villous adenomas are known to cause depletion syndrome, also referred to as the McKittrick-Wheelock syndrome, a condition characterised by secretory diarrhoea, dehydration, hyponatremia, hypokalaemia, hypochloraemia, metabolic acidosis and acute renal failure. Prostaglandin-E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…6,8 Some studies have shown the usefulness of indomethacin and somatostatin especially for poor surgical candidate. 4,9,10 The case we described meets the diagnostic criteria of MKS, such secretory diarrhea due to villous adenoma, acute renal failure and electrolyte and acid-base disorders. Clinical features were similar to those already reported in literature.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…6,8 Some studies have shown the usefulness of indomethacin and somatostatin especially for poor surgical candidate. 4,9,10 The case we described meets the diagnostic criteria of MKS, such secretory diarrhea due to villous adenoma, acute renal failure and electrolyte and acid-base disorders. Clinical features were similar to those already reported in literature.…”
Section: Discussionmentioning
confidence: 79%
“…6,7 According to literature most of reported cases are due to villous adenoma, with some cases secondary to adenocarcinoma or neuroendocrine tumor. 8 Only a little percentage (0.76-2.4%) of villous adenomas become secretory 4 and the etiopathogenesis of this process is not completely clear. Secretory and nonsecretory villous adenomas show differences on microscopic and ultrastructural examinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, endoscopic submucosal dissection has been reported to be feasible and useful for MWS treatment (8). In another study, it was reported that the symptoms of MWS may be reduced 48 hours after the start of indomethacin therapy (9). Transabdominal laparoscopic procedures are the most described methods in the treatment of MWS.…”
Section: Discussionmentioning
confidence: 99%